Multiple game trading strategy of multiple virtual power plants considering carbon trading - Chu, Tianfeng; An, Xingchen; Zhu, Yu; Wang, Xueying; Deng, Limin (Frontiers in Energy Research, 2023)
Because the large-scale access of distributed energy resources has a certain impact on the power grid, and distributed energy resources cannot participate in the power market transactions alone. Based on this, the concept of virtual power plant (VPP) has emerged, which can aggregate distributed power sources and controllable loads in the region for coordinated regulation. The trading of virtual power plant should not only consider the economy, but consider its low carbon degree. Therefore, this paper constructs a unified bidding strategy of Multi-VPPs that considers carbon-electricity integration trading. This paper designs a multi-game trading strategy among Multi-VPPs to achieve their unified trading, after each VPP determines the internal trading strategy. Finally, through simulation, it is verified that the multiple game strategy between Multi-VPPs considering carbon trading proposed in this paper can effectively improve the efficiency and trading income of VPP, and promote the consumption of new energy.